Berpikir Matematika dalam Al-Qur’an: Pemahaman tentang Penciptaan dan Ketertiban Alam - Izzi Munaya Putri; Ali Akbar (Jurnal test, 2024)
This research aims to analyze the verses of the Qur'an more deeply regarding the creation and order of the universe, linking them with mathematical concepts, and attempting to integrate them with modern physics findings. This study employs library research, which falls under qualitative descriptive research. The author collects literature data to record, read, and manage research materials consisting of articles on mathematics and physics from an Islamic perspective, the Qur'an, and interpretations. The results show that the Qur'an provides profound insights into the marvels of the universe's creation by Allah. Concepts such as the creation of the heavens and the earth aligning with the Big Bang theory, as well as the implications of Newton's gravitational principles in maintaining the stability of the universe, analogies about the earth as a place of rest or swing also reflect scientific discoveries about the rotation and revolution of the earth. Furthermore, the process of rainfall and the water cycle, as well as descriptions of two seas meeting but not mixing, indicate harmony in the universe. Finally, interpretations of scientific principles such as tidal phenomena as part of the signs of Allah's power in governing the universe are also found in the Qur'an.